The Battle for Patent Rights in Plant Biotechnology: Evidence from Opposition - Cédric Schneider (Copenhagen Business School (CBS), Department of Economics, 2010)
This paper describes and analyzes the occurrence and extent of oppositions initiated against plant biotechnology patents granted by the European Patent Office (EPO). The opposition mechanism is a legal procedure that allows any third party to challenge the validity of patents awarded by the EPO. Results indicate that the opposition rate is far greater in plant biotechnology than in other emerging industries. Consistent with theoretical predictions, the empirical findings suggest that opposed patents are disproportionately those that score high on features that proxy for their “value” or “quality”. In contrast to previous findings, however, the results show that large-volume applicants are more likely to be opposed. Because the boundaries of plant biotech patents are ill-defined, large patent portfolios do not promote cooperative behavior such as licensing or settlements. The analysis rejects the hypothesis that awardees are subject to “nuisance” or “frivolous” oppositions. Instead, the opposition procedure serves as an error correction mechanism.
hdl:10398/8220
Keywords: K41; L65; O34; 330; litigation; biotechnology; patents